Screening of glycoside hydrolases and ionic liquids for fibre modification. Issue 3 (1st November 2017) - Rahikainen, Jenni; Anbarasan, Sasikala; Wahlström, Ronny; Parviainen, Arno; King, Alistair WT; Puranen, Terhi; Kruus, Kristiina; Kilpeläinen, Ilkka; Turunen, Ossi; Suurnäkki, Anna
Abstract: BACKGROUND: This study elaborates the possibility to apply combined ionic liquid (IL) and enzyme treatments for pulp fibre modification. The approach involves swelling of fibre surfaces with IL followed by enzymatic modification of the disrupted fibre surface using carbohydrate active enzymes. RESULTS: The capacity of seven cellulose‐dissolving or cellulose‐swelling ionic liquids to swell pulp fibres was compared. In addition, thirteen cellulases and five xylanases were screened for their IL tolerance, which determines their applicability in combined or sequential IL–enzyme treatments of fibres. Among the studied ionic liquids, 1‐ethyl‐3‐methylimidazolium dimethylphosphate ([EMIM]DMP) and 1, 3‐dimethylimidazolium dimethylphosphate ([DMIM]DMP) had the strongest effect on fibre swelling. These solvents were also found to be the least inactivating for the studied enzymes. CONCLUSION: Enzyme compatibility and cellulose‐dissolving capability are not two conflicting properties of an ionic liquid. © 2017 Society of Chemical Industry